Prognostic significance of D-dimer, neuron-specific enolase, and lactate dehydrogenase changes in patients with severe traumatic brain injury: a logistic regression analysis - Jing Xie; Lu Zhang; Ning Gan (Journal of the Pakistan Medical Association)
The retrospective study was conducted at Baoding No.1 Central Hospital, China, and comprised data from July 2021 to January 2023, and aimed at exploring the relationship of neuron-specific enolase, D-dimer and lactate dehydrogenase with prognosis in patients with serous traumatic brain injury. Data of 100 patients was categorised into favourable prognosis group A having 50(50%) patients and unfavourable prognosis group B having 50(50%) patients, and was compared with as many healthy controls in group C. Increase in neuron-specific enolase, D-dimer and lactate dehydrogenase concentrations was significantly elevated in groups A and B compared to group C (p<0.05), and in group B compared to group A (p<0.05).